A Study on Anatomical features of Acalypha paniculata Miq. – A medicinal plant - K. Bhavadharaniparkavi; P. Abirami (International Journal of Pharma and Bio Sciences, 2020)
Euphorbiaceae is a largest family of flowering plants represented by about 61 genera and 336 species in India, abundantly distributed in the tropical regions. It is also called a spurge family, which includes trees, shrubs and herbs. The study was aimed to explore the anatomical characters of Acalypha paniculata Miq. leaf, stem and root. The Acalypha paniculata is an erect herb with minute hairs mostly distributed in the shady moist places. Flowers are monoecious, fruit capsule with globose seeds. The microscopical observation showed the presence of multicellular, uniseriate, non-glandular trichomes and paracytic stomata. The transverse section of leaf showed the three vascular bundles, collateral, semicircular in outline and have long parallel compact vertical lines of thick walled circular xylary elements and small units of discrete phloem elements below. The transverse section of stem showed the calcium oxalate crystals as spherical spiny bodies. In the centre of the root there is a dense cluster of small vessels and wide vessels. The powder microscopy reveals the clumps of xylem bundles, parenchyma cells, trichomes, vessels and sieve tubes. The study plant A. paniculata is used to treat kidney diseases, hernia, stomach ache, anaemia and antidote. In India, the plant is used as the vegetable. The vascular bundles are three in number in the centre of petiole of Euphorbia genus, the same were reported in the present study also. The pharmacognostical investigation of Acalypha paniculata could be used for the proper identification, determination of its quality, purity and detection of adulteration.